The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1175/jcli-d-14-00564.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of High-Frequency Atmospheric Forcing on the Circulation and Deep Convection of the Labrador Sea

Abstract: The influence of high-frequency atmospheric forcing on the circulation of the North Atlantic Ocean with emphasis on the deep convection of the Labrador Sea was investigated by comparing simulations of a coupled ocean-ice model with hourly atmospheric data to simulations in which the high-frequency phenomena were filtered from the air temperature and wind fields. In the absence of high-frequency atmospheric forcing, the strength of the Atlantic meridional overturning circulation and subpolar gyres was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…Noticeably, most of the winds with wind speed ≥10 m/s, which are commonly associated with transitory storms (Wang et al, ), are smoothed out by the low‐pass filter. The temperature peaks associated with high‐frequency atmospheric phenomena are also reduced, but the daily mean temperature is not significantly affected by the filter (Figure c) in agreement with Holdsworth and Myers (). Hence, with the purpose of highlighting the difference in the atmospheric forcing between the CONTROL and CALM simulations, we hereafter adopt “high‐frequency winds” to refer the “high‐frequency atmospheric phenomena,” which are absent in the CALM simulation.…”
Section: Methodssupporting
confidence: 86%
“…Noticeably, most of the winds with wind speed ≥10 m/s, which are commonly associated with transitory storms (Wang et al, ), are smoothed out by the low‐pass filter. The temperature peaks associated with high‐frequency atmospheric phenomena are also reduced, but the daily mean temperature is not significantly affected by the filter (Figure c) in agreement with Holdsworth and Myers (). Hence, with the purpose of highlighting the difference in the atmospheric forcing between the CONTROL and CALM simulations, we hereafter adopt “high‐frequency winds” to refer the “high‐frequency atmospheric phenomena,” which are absent in the CALM simulation.…”
Section: Methodssupporting
confidence: 86%
“…Finally, previous modeling studies have shown that the deep winter MLDs in the Labrador Sea are highly sensitive to subseasonal wind forcing (Holdsworth and Myers, ; Wu et al, ). We also find that deep mixing in the Labrador Sea is highly sensitive to subseasonal winds, but we also show that other sites of deep MLDs around the globe are not especially sensitive to subseasonal winds.…”
Section: Discussionmentioning
confidence: 88%
“…However, suppressing the effects of intrinsic oceanic variability by averaging all these grid points into regional hot spots shows that the seasonal cycle of MLD is reduced in the LP scenario (relative to CTL) in all these regions (Figure ). The Labrador Sea is most notable (as in Holdsworth and Myers, ). There, the seasonal cycle amplitude exceeds 1,000 m in some locations, and the subseasonal winds are crucial to sustaining this large seasonal cycle amplitude in CTL.…”
Section: Resultsmentioning
confidence: 99%
“…A map of the model domain with the respective horizontal grid resolution is shown in Figure a. This regional configuration has been used in the past for studying the circulation and deep convection in the Labrador Sea [ Holdsworth and Myers , ] and the spreading of Greenland freshwater in the subarctic seas [ Dukhovskoy et al ., ]. The model domain of this configuration covers the whole North Atlantic and the Nordic Sea (including the Gulf of Mexico in the west and the Mediterranean Sea in the east) with open boundaries at 20°S and the Bering Strait.…”
Section: Methodsmentioning
confidence: 99%